Effects of Ginger on Growth Indices and Pb Bioaccumulation of Tomato Fruits Cultivated in Lead and Spent Engine Oil-Contaminated Soils - Olaniyi, Amoo Abdulhamid; Stephen, Ezeonu Chukwuma; John, Umaru Isaac (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Good soil is needed for public health and this research studies lead concentrations of tomato planted in different soil samples in Wukari, Taraba state, Nigeria (with 50mg/kg simulated and non-simulated contamination) labelled groups A-H. Two weeks-old tomato seedlings were transplanted to triplicates of soils pots labelled A: normal soil, B:Ginger treated (positive control), three negative controls; C:lead contaminated; D Spent Engine Oil (SEO) contaminated, and E:Pb+SEO containing soil, F:Lead contaminated+ginger treatment, G: SEO contaminated+ginger treatment, H:lead+SEO contaminated+ginger treatment. The lengths, circumferences and weights of 36 tomato fruits per plant pot were measured at random. Lead uptake and bioaccumulation were also assessed in tomato fruits derived from each group. Tomato fruits in group E weighed highest (15.41±7.81g) while those in group H had the lowest weight (12.02±6.69g). The longest and the highest average tomato fruit circumference were recorded in group D (5.61±2.66cm and 6.15±2.93cm) respectively. Conversely, group H presented the shortest mean tomato fruits with 4.19±2.45cm and lowest fruit circumference (4.49±2.34cm). Bioaccumulation of lead was highest in tomatoes of group E with 1.79±0.47ppm and the lowest was derived from group A:normal soil with 0.68±0.13ppm on average each. The lead concentrations of all groups exceeded permissible limits specified in WHO/FAO Standards (0.01 ppm) as well as the maximum allowable concentration of 0.02 ppm by EU and 0.05 ppm limit set by USEPA suggesting a public health concern.